2019
DOI: 10.1101/791871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglial depletion with CSF1R inhibitor during chronic phase of experimental traumatic brain injury reduces neurodegeneration and neurological deficits

Abstract: Chronic neuroinflammation with sustained microglial activation occurs following moderate-to-severe traumatic brain injury (TBI) and is believed to contribute to subsequent neurodegeneration and neurological deficits. Microglia, the primary innate immune cells in brain, are dependent on colony stimulating factor 1 receptor (CSF1R) signaling for their survival. In this translational study, we examined the effects of delayed depletion and subsequent repopulation of microglia on chronic neurodegeneration and funct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 72 publications
(103 reference statements)
4
43
0
Order By: Relevance
“…Neuroinflammation and gliosis can often persist for months or even years post-brain trauma 7 , 9 , and interventions aimed at attenuating this neuroinflammation have proven successful in modulating cognitive outcomes 61 , 62 . Yet, the physiological processes involved in the prolonged inflammatory state of the TBI brain remain poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation and gliosis can often persist for months or even years post-brain trauma 7 , 9 , and interventions aimed at attenuating this neuroinflammation have proven successful in modulating cognitive outcomes 61 , 62 . Yet, the physiological processes involved in the prolonged inflammatory state of the TBI brain remain poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…To specifically ablate microglia cells in the brain we used the small molecule compound PLX5622, that is a potent inhibitor of the colony-stimulating factor 1 receptor (CSF1R) [ 50 ]. CSF1R inhibitors are widely used to study the role of microglia in several diseases [ 51 ā€“ 53 ] including neurodegenerative disease as AD [ 31 , 32 , 50 , 54 ], and we and others previously showed that four weeks of treatment with the CSF1R inhibitor PLX5622 depleted microglia in WT and APP-PS1 mice [ 31 , 32 , 35 ]. In this previous experiment, we had treated APP-PS1 and WT mice with either control or PLX5622 chow for a total of 28 days (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…149,150 However, injury models, such as traumatic brain injury (TBI), can cause BBB breakdown and subsequent infiltration of immune cells into the brain. 151,152 Likewise, AD pathology is also thought to propagate the loss of BBB integrity. 153 Microglial depletion and repopulation after TBI has been reported to replace chronically activated microglia with resting-state myeloid cells, resulting in decreased neuroinflammation and neuronal loss.…”
Section: Ad Immune Cells: Microglia or Macrophages?mentioning
confidence: 99%
“…153 Microglial depletion and repopulation after TBI has been reported to replace chronically activated microglia with resting-state myeloid cells, resulting in decreased neuroinflammation and neuronal loss. 151 The neuroprotection conferred by the repopulated myeloid cells post-TBI relies on their induction of IL-6 trans-signaling to enhance learning and memory. 154 Therefore 156 What underlies the discrepancies between these two studies remains to be fully resolved.…”
Section: Ad Immune Cells: Microglia or Macrophages?mentioning
confidence: 99%